Menyibak Pelaporan Aset Bersejarah Berdasarkan Psap No. 07 Tahun 2010 (Studi Fenomenologi Pada Candi Penataran Blitar-Jawa Timur) - Diana Elvianita M (Universitas Islam Balitar, 2016)
Historic assets are historic buildings, monuments, archaeologicalplaces like temples, and the work is focused on reporting seni.Penelitianhistoric assets Temple Penataran.Candi Penataran selected as the objectof this study, because the temple Upgrading an historic assets inIndonesia and is the largest in the temple kemplek East Java. It is hopedthat by doing this research can provide answers on